Answer:
f(x) = A*∛(x + 2) + 3
Step-by-step explanation:
Suppose a generic cube as:
f(x) = A*∛(x - b) + C
We will have a turning point at the x value:
x = b
Then if we have a turning point at (-2, 3)
This means that the turning point is at x = -2 and y = 3
Then b = -2
And our cube root function will be something like:
f(x) = A*∛(x - (-2)) + C
f(x) = A*∛(x + 2) + C
And we know that f(-2) = 3
then:
f(-2) = A*∛(-2 + 2) + C = 3
f(-2) = A*∛(0) + C = 3
= C = 3
Then the general equation will be something like:
f(x) = A*∛(x + 2) + 3